Elements of Promotional Discourse in English-Language Academic Abstracts - I. P. Khoutyz (Научный диалог, 2024)
This article focuses on identifying elements of promotional discourse within Englishlanguage abstracts. The research corpus comprises ten abstracts from highly cited articles published in the Journal of Linguistics. It is demonstrated that at the lexical level, the promotional aspect is represented by specialized terminology and vocabulary that emphasizes the experimental nature of the research. Additionally, it is established that grammatical features of the abstract are realized through action-oriented verbs, present tense, a combination of active and passive voice, and the use of the pronoun “we,” which the authors employ to construct a dialogue with the reader. The analysis reveals that the sentences in the abstracts are complex and contain clarifying information. Notably, parallel constructions and enumerations — expressive syntactic techniques — are introduced in the abstracts to enhance the significance of the research findings. At the linguo-pragmatic level, references to sources, quantitative data, contextualization of the study, and contrasts are highlighted. All of these techniques are interpreted as aimed at representing specific attributes of the scientific work: high significance, breadth, reliability, and overcoming the limitations of previous research by colleagues. The conclusion is drawn that the promotional features of the abstract may be expressed implicitly; however, as is characteristic of promotional texts, they are directed towards attracting attention to both the research and the author.